Dynamics and enhanced stability properties of slender leaching tubings in salt cavern storage with a Y-type manifold fitted at free downstream end. (November 2021) - Ge, Xinbo; Li, Yinping; Shi, Xilin; Ma, Hongling; Wang, Kun; Yin, Hongwu
Highlights: A fluid-conveying pipe model is established for dynamics analysis of the leaching tubing with a Y-type manifold. It is found by calculation that dimensionless critical flow velocities are increased with increasing θ . Several experiments are performed by using silicone–rubber pipes fitted with plastic Y-type manifolds with inclined angle θ = π/3 or π/2. The stability is enhanced for silicone–rubber pipes, due to the Y-type manifold, specifically, when θ = π/2. Abstract: Currently, the construction of salt cavern storages in China generally adopts solution mining technology with single-well convection and using a diesel cushion, however, leaching tubing is occasionally subjected to excessive bending and/or breaking during leaching process. Leaching tubing failure leads to the cavern shape being out of control or even scrapped. In this paper, regarding the leaching tubing as vertical hanging pipes conveying fluid, the dynamic equation of the leaching tubing with a Y-type manifold installed at the lower free end is established. The equation of motion is solved by means of Galerkin's truncation approximation method, and the dynamic response of the leaching tubing and the characteristics of the enhanced stability of the manifold are investigated. Since the downstream Y-type manifold has a select of the inclination angle, it is found through theoretical calculations that the flutter instability flow velocity of the fluid-conveying pipe can be conveniently controlled. The physical model experiment verifies that the Y-type manifold has a better enhancement effect on the stability of the leaching tubing. The proposed Y-type manifold may be helpful for the design and improvement of leaching tubing systems in the construction of salt cavern storage and salt mining.